Mixing Characteristics Of Gas-Liquid Flow In A Static Mixer: A Numerical Study - Ryan Anugrah Putra (Institut Teknologi Dirgantara Adisutjipto, 2020)
Mixing characteristics of gas-liquid co-current upward flow inside a vertical pipe equipped with a helical static mixer element were numerically investigated. The results from computational fluid dynamics (CFD) simulations with Euler-Euler model of three different length to diameter ratio (L/D) of the static mixer elements were compared. All simulated static mixers provide a better mixing condition in the comparison with the one without a static element. The sudden increase of rotational strength indicated by the liquid velocity curl was observed once the gas-liquid flows enter the static-mixer element zone. The smallest L/D static mixer provides the highest liquid velocity curl in the smallest axial distance providing the most effective mixing process among the tested elements. The best mixing characteristics shown by radial gas distribution was achieved with the static mixer with a smallest L/D.